2012
DOI: 10.7453/gahmj.2012.1.5.013
|View full text |Cite
|
Sign up to set email alerts
|

Resilience Training Program Reduces Physiological and Psychological Stress in Police Officers

Abstract: Research suggests that police work is among the most stressful occupations in the world and officers typically suffer a variety of physiological, psychological, and behavioral effects and symptoms. Officers operating under severe or chronic stress are likely to be at greater risk of error, accidents, and overreactions that can compromise their performance, jeopardize public safety, and pose significant liability costs to the organization. Therefore, this study explored the nature and degree of physiological ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
173
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(184 citation statements)
references
References 72 publications
6
173
0
5
Order By: Relevance
“…(), Grant et al . (), Jennings, Frank, Snowberg, Coccia, and Greenberg (), Liossis, Shochet, Millear, and Biggs (), McCraty and Atkinson (), Millear, Liossis, Shochet, Biggs, and Donald (), Pidgeon et al . (), Pipe et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(), Grant et al . (), Jennings, Frank, Snowberg, Coccia, and Greenberg (), Liossis, Shochet, Millear, and Biggs (), McCraty and Atkinson (), Millear, Liossis, Shochet, Biggs, and Donald (), Pidgeon et al . (), Pipe et al .…”
Section: Resultsmentioning
confidence: 99%
“…The resilience training interventions ranged from a single 90‐min session (Sood et al ., ) to 13 weekly sessions (Burton et al ., ). Other programmes were delivered over a two‐and‐a‐half‐day retreat (Pidgeon et al ., ), 3 weeks (Pipe et al ., ), 4 weeks (Jennings et al ., ), 5 weeks (Waite & Richardson, ), 6 weeks (Sherlock‐Storey et al ., ), 7 weeks (Liossis et al ., ), 10 weeks (Abbott et al ., ; Arnetz et al ., ; Grant et al ., ), 11 weeks (McCraty & Atkinson, ; Millear et al ., ), and 12 weeks (Carr et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…It follows then that the core component of improving use of force decision making is to improve an officer's ability to maintain an optimal state of sensory awareness (e.g., visual, auditory, tactile, olfactory) associated with moderate arousal during critical incidents (Kalisch et al, 2015). Controlling ones' heart rate within a moderate range is of key importance in maintaining physiological control, cognitive acuity, and the ability to perform under pressure (McCraty & Atkinson, 2012;McCraty et al, 2009). To examine if that goal was achieved by our intervention, the first step was to make sure that the testing scenarios induced significant physiological stress arousal.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that providing emotional self-regulation skills combined with heart rhythm coherence training results in significant improvements in communication, employee satisfaction, productivity, problem solving, reduced turnover, and a significant return on investment, both financially and socially (15, 67, 73, 86, 9092). In our experience, the self-regulation and resilience building training programs are most successful when leadership openly models and support the programs (93).…”
Section: Training Programs To Increase Social Coherencementioning
confidence: 99%